2017
DOI: 10.3390/toxins9120408
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Inhibition of Fusarium Pathogens and Biological Modification of Trichothecenes in Cereal Grains

Abstract: Fungi of the genus Fusarium infect cereal crops during the growing season and cause head blight and other diseases. Their toxic secondary metabolites (mycotoxins) contaminate grains. Several dozen toxic compounds produced by fungal pathogens have been identified to date. Type B trichothecenes—deoxynivalenol, its acetyl derivatives and nivalenol (produced mainly by F. graminearum and F. culmorum)—are most commonly detected in cereal grains. “T-2 toxin” (produced by, among others, F. sporotrichioides) belongs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Other bacteria such as species of Pseudomonas , Arthrobacter , Blastobacter , and those from the family Rhizobiaceae, have also been employed in the elimination of T-2 toxin with 100% efficiency recorded. However, Wachowska et al [39] reported that degradation products such as Neosolaniol (NEO), T-2 tetraol, and T-2 Triol were produced. These T-2 degradation products and residual parent toxins are capable of inducing apoptosis [40].…”
Section: Resultsmentioning
confidence: 99%
“…Other bacteria such as species of Pseudomonas , Arthrobacter , Blastobacter , and those from the family Rhizobiaceae, have also been employed in the elimination of T-2 toxin with 100% efficiency recorded. However, Wachowska et al [39] reported that degradation products such as Neosolaniol (NEO), T-2 tetraol, and T-2 Triol were produced. These T-2 degradation products and residual parent toxins are capable of inducing apoptosis [40].…”
Section: Resultsmentioning
confidence: 99%
“…Although several bacteria communities are capable of metabolizing T-2 (Dohnal et al 2008 ; Wachowska et al 2017 ) and can be abundant in the T. molitor microbiome (Garofalo et al 2019 ), their potential to metabolize all incidental toxins is unknown. Excretion of mycotoxins appears to occur through the larval faeces (Niermans et al 2019 ; Ochoa Sanabria et al 2019 ; Van Broekhoven et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a finer crushing of the maize straw allows quick colonization by soil-borne fungi and bacteria. Diverse interactions with these soil microorganisms regulate the growth of Fusarium fungi through direct, indirect, and mixed-path mechanisms (Wachowska et al 2017). Whereas in the literature, mainly antagonistic effects of the soil microbiome against Fusarium species are described (Wachowska et al 2017), the present results indicate a species-specific increase.…”
Section: Discussionmentioning
confidence: 44%